2010
DOI: 10.1002/14651858.cd006562.pub2
|View full text |Cite
|
Sign up to set email alerts
|

5-FU for genital warts in non-immunocompromised individuals

Abstract: The reviewed trials were highly variable in methods and quality, and the evidence provided by these studies was weak. Cure rates with several treatments were variable, and although 5-FU presents therapeutic results that are inferior to those seen with 5-FU + Inf alpha-2a (high dose) and 5-FU + CO2 Laser + Inf alpha-2a (high dose), the treatment should not be abandoned. Topical treatment with 5-FU has a therapeutic effect; however, the benefits and risks have not been determined clearly and further studies are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 48 publications
1
26
0
1
Order By: Relevance
“…A Cochrane review concluded that it is superior to placebo in achieving wart clearance but the authors state that the evidence provided by the current studies is weak. 83 It cannot be recommended for first-line use, but may be considered when other treatments have failed.…”
Section: Treatmentsmentioning
confidence: 99%
“…A Cochrane review concluded that it is superior to placebo in achieving wart clearance but the authors state that the evidence provided by the current studies is weak. 83 It cannot be recommended for first-line use, but may be considered when other treatments have failed.…”
Section: Treatmentsmentioning
confidence: 99%
“…A great number of reports have described good result with topical therapies: monochloracetic, bichloroacetic, and trichloroacetic acids, lactic, formic or salicylic acids; squaric acid dibutyl ester; imiquimod, fluorouracil or zinc sulphate; cidofovir; cryotherapy; cantharidin, surgical curettage, photodynamic therapy, and pulsed-dye or carbon dioxide laser (1,2). Systemic administration of cimetidine, levamisole, hydroxychloroquine, oral isotretinoin have been proven to be effective in recalcitrant warts (1,3).…”
Section: Discussionmentioning
confidence: 99%
“…Seventy one percent of patients treated with 5-FU had complete resolution of their anogenital warts versus 23% of patients treated with placebo. One of those studies reported a recurrence of lesions in one patient who originally had complete resolution [44]. 5-FU can be administered as a topical gel or by intralesional injection.…”
Section: Antimitotic Therapymentioning
confidence: 99%